RNA-binding proteins and heat-shock protein 90 are constituents of the cytoplasmic capping enzyme interactome - Trotman, Jackson B. (J Biol Chem, 2018)
The N(7)-methylguanosine cap is added in the nucleus early in gene transcription and is a defining feature of eukaryotic mRNAs. Mammalian cells also possess cytoplasmic machinery for restoring the cap at uncapped or partially degraded RNA 5′ ends. Central to both pathways is capping enzyme (CE) (RNA guanylyltransferase and 5′-phosphatase (RNGTT)), a bifunctional, nuclear and cytoplasmic enzyme. CE is recruited to the cytoplasmic capping complex by binding of a C-terminal proline-rich sequence to the third Src homology 3 (SH3) domain of NCK adapter protein 1 (NCK1). To gain broader insight into the cellular context of cytoplasmic recapping, here we identified the protein interactome of cytoplasmic CE in human U2OS cells through two complementary approaches: chemical cross-linking and recovery with cytoplasmic CE and protein screening with proximity-dependent biotin identification (BioID). This strategy unexpectedly identified 66 proteins, 52 of which are RNA-binding proteins. We found that CE interacts with several of these proteins independently of RNA, mediated by sequences within its N-terminal triphosphatase domain, and we present a model describing how CE-binding proteins may function in defining recapping targets. This analysis also revealed that CE is a client protein of heat shock protein 90 (HSP90). Nuclear and cytoplasmic CEs were exquisitely sensitive to inhibition of HSP90, with both forms declining significantly following treatment with each of several HSP90 inhibitors. Importantly, steady-state levels of capped mRNAs decreased in cells treated with the HSP90 inhibitor geldanamycin, raising the possibility that the cytotoxic effect of these drugs may partially be due to a general reduction in translatable mRNAs.